Civil Law in Market Governance: Legal Instruments, Economic Policy, and State Power - Shohib Muslim (PT. Anagata Sembagi Education, 2025)
Modern market governance is no longer shaped solely by free market mechanisms but increasingly relies on state intervention through legally institutionalized economic policies. In this context, civil law—particularly through contracts, property rights, and civil liability—has become a strategic instrument for directing market behavior. This development generates normative ambiguity in positive law concerning the boundary between civil law as private law and as a tool of market governance, the legitimacy of using private law instruments to implement economic policy, and the relationship between freedom of contract and public interest–based economic regulation. Employing normative legal research with statute, conceptual, and case approaches, this article examines the role of civil law in market governance and the juridical implications of state intervention through private law instruments. The analysis demonstrates that unstructured instrumentalization of civil law undermines legal certainty and private autonomy while obscuring the limits of state power. This article argues for a normative reconstruction that positions civil law as a limited instrument of economic policy, grounded in conditional private autonomy, proportionality, and accountability, in order to balance economic efficiency, legal certainty, and social justice within market regulation.